Professional road cycling sprints: Quantifying the demands of the final hour - Menaspa, P.; Martin, D. T.; Quod, M.; Abbiss, C. R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The demands of uphill and time trial performances and the physiological characteristics of professional road cyclists have been well documented. Despite the importance of sprinting to the overall outcomes of a race and the high number of sprint finishes within professional road cycling (Menaspà et al. 2013a), research examining the demands of professional road sprint cycling is limited to a couple of preliminary studies (Menaspà et al. 2013a; Menaspà et al. 2013b). The aim of this study was to examine and describe the demands of road cycling sprint competitions in professional male cycling, with particular focus on the lead-up phase prior to the final sprint. Methods: Seventeen road race files from 6 professional male cyclists who placed in the top 5 (age, 27.0±3.8 y; height, 1.76±0.03 m; weight, 71.7±1.1 kg) were analysed. Power, cadence, speed and total elevation gain (TEG) were recorded throughout the race using an SRM power meter. Data were averaged over the final 60, 10 and 1 min prior to the sprint finish. Exposure Variation Analysis (EVA) was used to quantify variations in power during the final 10 min of the race. Results: The average (±SD) of all variables measured in this study significantly increased as athletes approached the finish line (p<0.001). Power, cadence, speed and TEG were 233±33 W, 89±4 rpm, 45.4±2.9 km/h and 218±192 m in the 60 min; 316±43 W, 95±4 rpm, 50.5±3.3 km/h and 27±37 m in the last 10 min; and to 487±58 W, 102±6 rpm, 55.4±4.7 km/h and 3±6 m in the 1 min. EVA revealed a significantly greater number of short duration and high intensity efforts (> 6.6 W/kg and <3.8 s) in the final 5 min, compared with the penultimate 5 min (p=0.010). Discussion: As expected, race intensity significantly increased as sprinters approached the finish line. Aerobic fitness is likely to be extremely important to road sprint cycling performance as evidenced by the elevation gain (up to 600 m/h of vertical ascension rate), high intensity and variability of the power output in the final hour leading-up to the sprint. These results expand upon previous research, highlighting that aerobic fitness is important for road sprinting. Therefore, coaches and cyclists interested in improving sprinting in road races should focus on aerobic as well as anaerobic qualities.